2016
DOI: 10.1038/srep28656
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization of excitons in organic multiferroic composites

Abstract: Recently, the discovery of room temperature magnetoelectricity in organic charge transfer complexes has reignited interest in the multiferroic field. The solution processed, large-area and low cost organic semiconductor materials offer new possibilities for the functional all organic multiferroic devices. Here we report the spin polarization of excitons and charge transfer states in organic charge transfer composites by using extended Su-Schrieffer-Heeger model including Coulomb interaction and spin-flip effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Moreover, due to the electron-phonon (chargelattice) coupling tightly related to the molecular assembly axes and spin cone orientation in CTC, this material exhibited anisotropic ferroelectricity, magnetization and ME coupling behavior (Figure 4). [30] Similar phenomena are also observed in the donor-acceptor segregated-stack CT cocrystals based on fullerene and other thiophene-based derivatives. [72,77] To be mentioned, a magnetoelastic character can also be realized in this polythiophene (P3HT) • C 60 system, where the saturation magnetization varies inversely with the applied static compression stress.…”
Section: -Based Ct Multiferroicssupporting
confidence: 55%
See 3 more Smart Citations
“…Moreover, due to the electron-phonon (chargelattice) coupling tightly related to the molecular assembly axes and spin cone orientation in CTC, this material exhibited anisotropic ferroelectricity, magnetization and ME coupling behavior (Figure 4). [30] Similar phenomena are also observed in the donor-acceptor segregated-stack CT cocrystals based on fullerene and other thiophene-based derivatives. [72,77] To be mentioned, a magnetoelastic character can also be realized in this polythiophene (P3HT) • C 60 system, where the saturation magnetization varies inversely with the applied static compression stress.…”
Section: -Based Ct Multiferroicssupporting
confidence: 55%
“…[19][20] The Ren group has done lots of explorations on the C 60 -based organic CT multiferroics. [29][30][31][32][33][34]77,82] A segregated-stack cocrystal with a long-range ordered CT network based on the electron donor TTF and acceptor C 60 was observed to display an unusual multitude of external stimulicontrolled ferroic properties, due to the modulation of chargespin composite orders (Figure 3a, b). [34] The density of singlet and triplet CT can be tuned by the magnetic field owing to the formation rate of spin-parallel and spin-antiparallel states for the competition of spin-conserving and spin-mixing.…”
Section: -Based Ct Multiferroicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that organic charge transfer complex does not have 3d electrons. Based on computational modeling, the origin of magnetism is resulted from electrons in organic acceptor to induce localized spin polarization . However, the other theoretical study showed that hole spins alignment in donor section will induce localized spin polarization, which is responsible for the origin of room temperature ferromagnetism .…”
Section: Introductionmentioning
confidence: 99%